(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
Ethanol and aqueous extracts of stem bark of Boswellia dalzielii was used to determine the phytochemical and antibacterial activity against enteropathogenic E. coli and S. dysenteriae. The extraction was carried out using a standard method. The phytochemical screening was carried out through standard procedures and the extracts were further tested for antimicrobial activity using agar well diffusion method. Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) were also determined. Ethanol extract has the highest percentage yield of 22.26, the phytochemical tests revealed the presence of saponins, tannins, flavonoids, terpenoid, glycosides, alkaloids, triterpenes, phenols and proteins. Antimicrobial activity shows that ethanol extract has the highest mean zone of inhibition of 17.67mm and 17. 00mm at the highest concentration (250mg/ml) against S. dysenteriae and E. coli respectively, both test organisms were resistant to all concentrations of aqueous extract except at the highest concentration. MIC of aqueous extract was 250mg/ml and MBC of 500mg/ml was shown on both the test organisms. The study shows that Boswellia dalzielii stem bark ethanol and aqueous extract contain bioactive components which are responsible for its antimicrobial activities and may have the potential for the development of plant source drugs against diarrhea causing E. coli and S. dysenteriae